Exploring the potential of graphene oxide functionalized with ionic liquid as sorbent in micro solid phase extraction towards steroids in water sample - Mohamad Hanapi, Nor Suhaila; Mohd Yusof, Raihana; Elias, Ezlan; Ramlan, Norlizayati; Ab Rani, Mohd Azri; Mastuli, Mohd Sufri (Faculty of Pharmacy, 2025)
Corticosteroids are widely used anti-inflammatory drugs but act as endocrine-disrupting compounds (EDCs), even at trace levels, posing serious health risks such as hormonal imbalances, reproductive issues, neurological disorders, and cancer. These contaminants enter water bodies mainly through improper disposal and household effluents, requiring efficient removal strategies. Conventional sorbents like silica have shown limited effectiveness, highlighting the need for a greener, more selective sorbent. Ionicliquids (ILs), with low volatility and high tunability, offer a promising approach to enhance sorbent performance. This study developed an Ionic LiquidGraphene Oxide (IL-GO) sorbent for micro-solid phase extraction and evaluated its efficiency in removing hydrocortisone, dexamethasone, and fluocinolone acetonide from water samples. Results showed that IL-GO achieved significantly higher extraction efficiencies for hydrocortisone and fluocinolone acetonide, along with remarkable adsorption capacity for dexamethasone, outperforming GO alone. These findings demonstrate the potential of IL-GO as an effective and selective sorbent for corticosteroid removal, contributing to improved water quality and environmental safety.